Antigen Specificity and Clinical Significance of IgG and IgA Autoantibodies Produced in situ by Tumor-Infiltrating B Cells in Breast Cancer - Garaud, Soizic; Zayakin, Pawel; Buisseret, Laurence; Rulle, Undine; Silina, Karina; de Wind, Alexandre; Van den Eyden, Gert; Larsimont, Denis; Willard-Gallo, Karen; Linē, Aija (Frontiers in Immunology, 2018)
An important role for tumor infiltrating B lymphocytes (TIL-B) in the immune response to cancer is emerging; however, very little is known about the antigen specificity of antibodies produced in situ. The presence of IgA antibodies in the tumor microenvironment has been noted although their biological functions and clinical significance are unknown. This study used a 91-antigen microarray to examine the IgG and IgA autoantibody repertoires in breast cancer (BC). Tumor and adjacent breast tissue supernatants and plasma from BC patients together with normal breast tissue supernatants and plasma from healthy controls (patients undergoing mammary reduction and healthy blood donors) were analyzed to investigate relationships between autoantibodies and the clinical, histological and immunological features of tumors. Our data show that >84% of the BC samples tested contain autoantibodies to one or more antigens on the array, with ANKRD30BL, COPS4 and CTAG1B being most frequently reactive. Ex vivo TIL-B responses were uncoupled from systemic humoral responses in the majority of cases. A comparison of autoantibody frequencies in supernatants and plasma from patients and controls identified eight antigens that elicit BC-associated autoantibody responses. The overall prevalence of IgG and IgA autoantibodies was similar and while IgG and IgA responses were not linked they did correlate with distinct clinical, pathological and immunological features. Higher levels of ex vivo IgG responses to BC-associated antigens were associated with shorter recurrence-free survival (RFS), HER2 overexpression and lower tumor-infiltrating CD8+ T cell counts. Higher IgA levels were associated with estrogen and progesterone receptor-negative cancers but were not significantly associated with RFS. Furthermore, ex vivo IgA but not IgG autoantibodies reactive to BC-associated antigens were linked with germinal center and early memory B cell maturation and the presence of tertiary lymphoid structures suggesting that these TIL-B are activated in the tumor microenvironment. Overall, our results extend the current understanding of the antigen specificity, the biological and the clinical significance of IgG and IgA autoantibodies produced by BC TIL-B in situ.